Agricultural information in the Congo - achieving something lasting and linking to the outside world - Ouenabio, Jean-Marie Samuel (Technical Centre for Agricultural and Rural Cooperation, 1989)
.Jean-Marie Samuel Ouenabio Jean-Marie Samuel Ouenabio Is an African Journalist who has chosen to work among the 'poor relations' of his trade: science and development. He was born in 1957, and is today in charge of the science magazine on the...